A study on the relationship of the interpupillary distance to the mesiodistal diameter of maxillary central incisor among 50 filipinos - Santos, Felicitas Beverly
In the study, fifty Filipinos ages 13 - 30 years old were chosen. The interpupi1lary distance was measured with an interpupi1lary ruler. The mesiodistal diameters of the central incisors were measured with a vernier caliper on their diagnostic cast. The averages of the measurements were statistically compared with the use of correlation coefficient and regression analysis. It was also subjected to f?test. The multiple R = 0.26. This indicates a weak correlation. The probability P = 0.06, meaning with a 0.05 alpha level, there is no significant relationship between the interpupi1lary distance and the mesiodistal diameter of the maxillary central incisors among 50 Filipinos.